Square acid complex-derived nickel-iron-based double-metal hydroxide, preparation method and electrode
By using nickel-iron-based bimetallic hydroxide derived from square acid complex in electrolytic hydrogen production technology, the high reaction energy barrier and slow kinetics of the anode oxygen evolution reaction are solved, high catalytic activity and high current stability are achieved, and the large-scale development of electrolytic green hydrogen production is promoted.
Patent Information
- Application Number
- CN202411780298.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-05
AI Technical Summary
In the existing electrolytic hydrogen production technology, the oxygen evolution reaction of the anode has a high reaction energy barrier and slow kinetics, resulting in high overpotentials, and the surface reconstruction phenomenon of the catalyst during the reaction process is complex, affecting the synthesis and design of the catalyst.
The nickel-iron-based bimetallic hydroxide derived from square acid complex has an interactive micron-scale pore structure on the surface, and is prepared by hydrothermal treatment and electrochemical activation reconstruction treatment to form a tightly bound catalyst structure.
It has achieved high catalytic activity and long-term large current stability, with an ultra-large current density up to 3000mA/cm2, and overcomes the harsh conditions under a large current environment. It has important practical significance for the large-scale development of electrolyzed water to make green hydrogen.
Smart Images

Figure CN119640314A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of new material synthesis and technology, and specifically relates to a nickel-iron-based double metal hydroxide derived from a square acid complex, a preparation method and an electrode. Background Art
[0002] Hydrogen production by water electrolysis is one of the key technologies for hydrogen production. At present, countries are focusing on developing hydrogen production by water electrolysis to improve the efficiency of electrolysis devices, reduce hydrogen production costs and expand the market scale. Hydrogen production by water electrolysis is expected to enable hydrogen energy to play a key role in the global energy transformation process. Using hydrogen energy, especially green hydrogen, to replace fossil fuels, some industries with high energy intensity are expected to achieve decarbonization.
[0003] The oxygen evolution reaction at the anode of water electrolysis has a large reaction energy barrier and slow kinetics, which is the main source of high overpotential in the process of water electrolysis. Therefore, the development of efficient oxygen evolution reaction catalysts has become the research focus of scholars at home and abroad. However, during the oxygen evolution reaction, the catalyst will undergo surface reconstruction, resulting in changes in the chemical structure and physical properties of the catalytic interface, which not only causes the dynamic evolution of the catalytic interface structure information, but also increases the complexity of the analysis of the structure-activity relationship of the real catalytic surface, resulting in one-sided analysis and conclusions, and limiting the synthesis and design strategies of efficient oxygen evolution catalysts. At the same time, due to the existence of the anodic oxidation reconstruction phenomenon, many metal ions or ligand molecules have not been taken seriously. Reversely using the anodic oxidation reconstruction phenomenon to assist in the construction of catalytic surface defects and molecular intercalation structures has also become an extremely innovative and challenging unconventional preparation method. At present, most of the existing research focuses on the intrinsic structure design of the initial catalyst, and often ignores the in situ dynamic evolution of the catalytic structure during the reaction.
[0004] At the same time, for the electrocatalytic water splitting process, current research often focuses on theoretical mechanism exploration and small-scale laboratory testing, and high-current test data that are truly oriented to industrial applications are in a state of vacancy. Under ampere-level high-current test conditions, the anode's interface microenvironment and gas-liquid transmission efficiency will significantly affect the activity and stability of the electrocatalyst. At present, most of the synthesis methods proposed in most studies are simply to mechanically deposit or load the catalyst on a self-supporting substrate material. The bonding between the catalyst and the surface of the substrate material is not strong. Due to the slow bubble diffusion and dense bubble impact under high current, the highest current density they reported is mostly concentrated at 600mA / cm 2 ~1000mA / cm 2 . Summary of the invention
[0005] In view of this, the object of the present invention is to provide a nickel-iron-based double metal hydroxide with high catalytic activity and long-term high current stability, at least partially solving the problems existing in the prior art. To achieve the object of the present invention, the present invention adopts the following technical solution:
[0006] The invention provides a nickel-iron-based double metal hydroxide derived from a squaric acid complex, which has an alternating micron-scale pore structure.
[0007] Furthermore, the pore structure width of the nickel-iron-based double metal hydroxide derived from the square acid complex is 4 microns to 8 microns.
[0008] The present invention also provides a method for preparing the nickel-iron-based double metal hydroxide derived from the square acid complex, comprising the following steps:
[0009] A. Pre-treating nickel foam;
[0010] B. hydrothermally treating the treated nickel foam in a solution of squaric acid and iron salt to obtain a nickel-iron-based squaric acid complex precursor;
[0011] C. The prepared nickel-iron-based square acid complex precursor is subjected to electrochemical activation and reconstruction treatment to obtain a nickel-iron-based double metal hydroxide derived from the square acid complex.
[0012] Furthermore, the thickness of the nickel foam in step 1 is 1 to 3 mm.
[0013] Furthermore, the iron salt described in step 2 is one of ferric nitrate, ferric chloride and ferric sulfate; the hydrothermal treatment temperature is 100-160° C., and the heating time is 4-8 hours; in the hydrothermal treatment solution, the molar ratio of square acid to iron salt is 5:1.
[0014] Furthermore, in step 3, the activation and reconstruction process of the nickel-iron-based square acid complex precursor is realized in an alkaline electrolyte by cyclic voltammetry.
[0015] Furthermore, the alkaline electrolyte is 1 mol / L potassium hydroxide; the activation voltage range is 1 to 1.45 V vs. RHE, and the activation cycle is 10 to 50 cycles.
[0016] Furthermore, the method further comprises vacuum drying the nickel-iron-based double metal hydroxide derived from the square acid complex; the drying temperature is 60-120° C.; and the drying time is 12-15 hours.
[0017] The present invention also provides nickel-iron based double metal hydroxide derived from the square acid complex prepared by the preparation method.
[0018] The present invention also provides an electrode, comprising a water electrolysis oxygen evolution catalyst, wherein the water electrolysis oxygen evolution catalyst is the nickel-iron-based double metal hydroxide derived from the above-mentioned square acid complex or the nickel-iron-based double metal hydroxide derived from the square acid complex obtained by the above-mentioned preparation method.
[0019] It can be seen from the above technical scheme that the present invention provides a nickel-iron-based double metal hydroxide derived from a square acid complex and a preparation method thereof and an electrode comprising a nickel-iron-based double metal hydroxide derived from a square acid complex. The surface of the nickel-iron-based double metal hydroxide derived from the square acid complex of the present invention has a natural pore structure that can promote the rapid transfer and transmission of hydroxide ions in the electrolyte, protons separated from the reaction intermediates, and product oxygen molecules to maintain high catalytic activity and long-term high-current stability. The preparation method of the nickel-iron-based double metal hydroxide derived from the square acid complex of the present invention is green, simple and efficient. The electrode comprising the nickel-iron-based double metal hydroxide derived from the square acid complex of the present invention is expected to overcome the harsh conditions under a large current environment, and has important practical significance for realizing the large-scale development of green hydrogen production by electrolysis of water. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0021] Figure 1 The XRD pattern of the nickel-iron-based square acid complex precursor prepared in Example 1;
[0022] Figure 2 The SEM image of the nickel-iron-based double metal hydroxide catalyst derived from the square acid complex prepared in Example 1;
[0023] Figure 3 TEM-Mapping image of the nickel-iron-based double metal hydroxide catalyst derived from the square acid complex prepared in Example 1. DETAILED DESCRIPTION
[0024] The embodiments of the present invention are described in detail below with reference to the accompanying drawings.
[0025] It should be noted that the following embodiments and features in the embodiments may be combined with each other in the absence of conflict; and, based on the embodiments in the present disclosure, all other embodiments obtained by ordinary technicians in the field without making any creative work are within the scope of protection of the present disclosure.
[0026] It should be noted that various aspects of the embodiments within the scope of the appended claims are described below. It should be apparent that the aspects described herein may be embodied in a wide variety of forms, and any specific structure and / or function described herein is merely illustrative. Based on the present disclosure, it should be understood by those skilled in the art that an aspect described herein may be implemented independently of any other aspect, and two or more of these aspects may be combined in various ways. For example, any number of aspects described herein may be used to implement the device and / or practice the method. In addition, other structures and / or functionalities other than one or more of the aspects described herein may be used to implement this device and / or practice this method.
[0027] The present invention provides a nickel-iron-based double metal hydroxide derived from a square acid complex supported by nickel foam, which can provide an interactive micrometer-level gas-liquid transmission channel and at least partially solve the problems existing in the existing electrolyzed water high current testing technology.
[0028] The invention provides a method for preparing a nickel-iron-based double metal hydroxide derived from a squaric acid complex. The method comprises the following steps: pre-treating a nickel foam mesh with an acid to remove surface oxides; hydrothermally treating the treated nickel foam mesh in a squaric acid and iron salt solution to obtain a nickel-iron-based squaric acid complex precursor; and electrochemically activating and reconstructing the precursor to obtain a nickel-iron-based double metal hydroxide derived from a squaric acid complex.
[0029] In an embodiment of the present invention, the acid pretreatment is 1 mol / L hydrochloric acid and 95% ethanol ultrasonic cleaning in sequence for 15 to 30 minutes.
[0030] In a specific embodiment of the present invention, the thickness of the nickel foam is 1 to 3 mm. Specifically, the thickness of the nickel foam is 1, 1.5, 2, 2.5, or 3 mm.
[0031] In a specific embodiment of the present invention, the iron salt is one of ferric nitrate, ferric chloride and ferric sulfate.
[0032] In an embodiment of the present invention, the temperature of the hydrothermal treatment is 100-160°C. The specific temperature can be 100°C, 120°C, 140°C, 160°C. The heating time can be 4 hours, 6 hours, or 8 hours. In some specific embodiments, the reaction temperature is 100°C and the heating time is 8 hours; in some specific embodiments, the reaction temperature is 120°C and the heating time is 6 hours; in some specific embodiments, the reaction temperature is 140°C and the heating time is 4 hours; in some specific embodiments, the reaction temperature is 160°C and the heating time is 4 hours.
[0033] In some embodiments, the molar ratio of the squaric acid to the iron salt in the hydrothermal treatment solution is 5:1.
[0034] In some embodiments, the hydrothermal treatment solution further comprises 0.3-0.5 g of polyvinyl pyrrolidone as a morphology directing agent.
[0035] In some embodiments, the present invention realizes the activation and reconstruction process of the nickel-iron-based square acid complex precursor in an alkaline electrolyte by cyclic voltammetry.
[0036] In some embodiments, the alkaline electrolyte is 1 mol / L potassium hydroxide; the activation voltage range is 1 to 1.45 V vs. RHE, and the activation cycle is 10 to 50 cycles.
[0037] In some embodiments, the preparation method of the present invention further comprises vacuum drying the nickel-iron-based double metal hydroxide derived from the squaric acid complex.
[0038] In some embodiments, the drying conditions of the present invention include: drying temperature of 60-120° C.; drying time of 12-15 h.
[0039] The preparation method of the present invention utilizes the acidic environment provided by the square acid complex to directly in-situ etch the nickel foam mesh to provide a nickel source. The self-source grown catalyst structure is more tightly and firmly combined with the self-supporting substrate and has natural micron-scale pores to accelerate bubble transmission.
[0040] The invention confirms the successful preparation of the nickel-iron-based squaric acid complex precursor by X-ray diffraction analysis, and characterizes the micron-scale channel structure of the nickel-iron-based double metal hydroxide derived from the squaric acid complex by scanning electron microscopy.
[0041] The present invention also provides an electrode, including a water electrolysis oxygen evolution catalyst, wherein the water electrolysis oxygen evolution catalyst is a nickel-iron-based double metal hydroxide derived from the above-mentioned square acid complex. The nickel-iron-based double metal hydroxide derived from the square acid complex of the present invention is used as an oxygen evolution electrocatalyst, which can provide an ultra-large current density of up to 3000mA / cm and long-term stability for hundreds of hours, overcomes the harsh conditions under a large current environment, and breakthroughs the current limit of the oxygen evolution reaction to 3000mA / cm, which has important practical significance for realizing the large-scale development of green hydrogen production by water electrolysis.
[0042] The present invention is described below in conjunction with specific embodiments, but the present invention is not limited to the following embodiments.
[0043] Example 1: Preparation of nickel-iron-based double metal hydroxide derived from square acid complex
[0044] Ultrasonic clean the nickel foam mesh with 1mol / L hydrochloric acid and 95% ethanol for 30 minutes and then put it into a vacuum drying oven to dry. Weigh 0.3g of polyvinyl pyrrolidone, 5mmol of squaric acid, and 1mmol of ferric nitrate nonahydrate and fully dissolve them in a polytetrafluoroethylene reactor containing 30mL of deionized water. Tilt the acid-washed nickel foam mesh into the above solution, assemble the reactor, heat it to 120℃ and maintain it for 6 hours. After the reaction is completed, rinse the product and dry it in a vacuum drying oven to obtain a nickel-iron-based squaric acid complex precursor.
[0045] Using a standard three-electrode system, the prepared precursor was subjected to cyclic voltammetry in a 1 mol / L potassium hydroxide electrolyte, with a scanning voltage range of 1-1.45 V vs. RHE (potential relative to the reversible hydrogen electrode); activated for 20 cycles. After the reaction was completed, the product was rinsed and dried in a vacuum drying oven at 120°C for 12 hours to obtain a nickel-iron-based double metal hydroxide derived from a square acid complex.
[0046] The obtained nickel-iron-based square acid complex precursor was characterized by XRD, such as Figure 1 As shown in the figure, the product has characteristic peaks belonging to metal square acid complexes, which proves the successful preparation of nickel-iron-based square acid complex precursor. Figure 2 As shown, the SEM image shows that a uniformly distributed micron-scale channel structure is formed on the surface of the skeleton structure of the foam nickel mesh, and the width of the channel structure is 4 to 8 microns. Figure 3 This is the TEM-Mapping image of nickel-iron based double hydroxide derived from square acid complex, which shows the uniform distribution of elements Ni, Fe, C and O.
[0047] Example 2: Preparation of nickel-iron-based double metal hydroxide derived from square acid complex
[0048] Ultrasonic clean the nickel foam mesh with 1mol / L hydrochloric acid and 95% ethanol for 30 minutes and then put it into a vacuum drying oven to dry. Weigh 0.3g of polyvinyl pyrrolidone, 5mmol of squaric acid, and 1mmol of ferric chloride and fully dissolve them in a polytetrafluoroethylene reactor containing 30mL of deionized water. Tilt the acid-washed nickel foam mesh into the above solution, assemble the reactor, heat it to 140℃ and maintain it for 4 hours. After the reaction is completed, rinse the product and dry it in a vacuum drying oven to obtain a nickel-iron-based squaric acid complex precursor.
[0049] Using a standard three-electrode system, the prepared precursor was subjected to cyclic voltammetry in a 1M / L potassium hydroxide electrolyte, with a scanning voltage range of 1-1.45V vs. RHE; activation was performed for 10 cycles. After the reaction was completed, the product was rinsed and dried in a vacuum oven at 100°C for 13h to obtain a nickel-iron-based double metal hydroxide derived from a square acid complex.
[0050] The obtained nickel-iron-based double metal hydroxide derived from the square acid complex was characterized by XRD and SEM, and the results were similar to those in Example 1.
[0051] Example 3: Preparation of nickel-iron-based double metal hydroxide derived from square acid complex
[0052] Ultrasonic clean the nickel foam mesh with 1mol / L hydrochloric acid and 95% ethanol for 30 minutes and then put it into a vacuum drying oven to dry. Weigh 0.3g of polyvinyl pyrrolidone, 5mmol of squaric acid, and 1mmol of ferric sulfate and fully dissolve them in a polytetrafluoroethylene reactor containing 30mL of deionized water. Tilt the acid-washed nickel foam mesh into the above solution, assemble the reactor, heat it to 100℃ and maintain it for 8 hours. After the reaction is completed, rinse the product and dry it in a vacuum drying oven to obtain a nickel-iron-based squaric acid complex precursor.
[0053] Using a standard three-electrode system, the prepared precursor was subjected to cyclic voltammetry in a 1M / L potassium hydroxide electrolyte, with a scan voltage range of 1-1.45V vs. RHE; activation was performed for 50 cycles. After the reaction was completed, the product was rinsed and dried in a vacuum drying oven at 60°C for 15h to obtain a nickel-iron-based double metal hydroxide derived from a square acid complex.
[0054] The obtained nickel-iron-based double metal hydroxide derived from the square acid complex was characterized by XRD and SEM, and the results were similar to those in Example 1.
[0055] Test Example 1:
[0056] At room temperature, the oxygen evolution performance of the catalyst sample prepared in Example 1 was tested in a 1M / L KOH solution using a three-electrode system on a Gamry Reference 3000 electrochemical workstation. The Pt sheet electrode was the counter electrode, the Hg / HgO electrode was the reference electrode, and the prepared catalyst was the working electrode. The linear sweep voltammetry (LSV) curve was obtained by scanning at a scan rate of 5 mV / s.
[0057] The preparation method of nickel-iron double metal hydroxide is to ultrasonically clean the nickel foam mesh with 1mol / L hydrochloric acid and 95% ethanol for 30 minutes, and then put it into a vacuum drying oven to dry to obtain a nickel foam mesh comparison sample. Weigh 0.6g of urea, 2mmol nickel chloride, and 1mmol ferric chloride and fully dissolve them in a polytetrafluoroethylene reactor containing 30mL deionized water. The acid-washed nickel foam mesh is tilted and immersed in the above solution, and the reactor is assembled, heated to 100°C and maintained for 8 hours. After the reaction is completed, the product is rinsed and dried in a vacuum drying oven to obtain the nickel-iron double metal hydroxide.
[0058] Table 1: Electrochemical oxygen evolution performance of the nickel-iron based double metal hydroxide derived from the square acid complex of the present invention
[0059]
[0060] The results show that the nickel-iron-based double metal hydroxide catalyst derived from the square acid complex prepared in Example 1 of the present invention has excellent oxygen evolution performance, and only needs an overpotential of 280mV, 315mV, and 337mV to provide 1000mA / cm 2 , 2000mA / cm 2 、3000mA / cm 2 The high current density far exceeds that of simple nickel-iron-based double metal hydroxide catalysts.
[0061] The oxygen evolution performance of the nickel-iron-based double metal hydroxide derived from the square acid complex prepared in Example 2 and Example 3 was tested by the same method. The results were similar to those of the nickel-iron-based double metal hydroxide catalyst derived from the square acid complex prepared in Example 1, and had excellent oxygen evolution performance, far exceeding that of a simple nickel-iron-based double metal hydroxide catalyst.
[0062] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the protection scope of the claims.
Claims
1. A nickel-iron-based double metal hydroxide derived from a square acid complex, characterized in that: It has an interactive micron-scale pore structure.
2. The nickel-iron-based double metal hydroxide derived from a square acid complex according to claim 1, characterized in that The width of the pore structure is 4 microns to 8 microns.
3. The method for preparing the nickel-iron-based double metal hydroxide derived from a square acid complex according to claim 1 or 2, characterized in that: The steps include: A. Pre-treating nickel foam; B. hydrothermally treating the treated nickel foam in a solution of squaric acid and iron salt to obtain a nickel-iron-based squaric acid complex precursor; C. The prepared nickel-iron-based square acid complex precursor is subjected to electrochemical activation and reconstruction treatment to obtain a nickel-iron-based double metal hydroxide derived from the square acid complex.
4. The preparation method according to claim 3, characterized in that: The thickness of the nickel foam in step 1 is 1 to 3 mm.
5. The preparation method according to claim 3 or 4, characterized in that: The iron salt described in step 2 is one or more of ferric nitrate, ferric chloride and ferric sulfate; the hydrothermal treatment temperature is 100-160° C., and the heating time is 4-8 hours; in the hydrothermal treatment solution, the molar ratio of squaric acid to iron salt is 5:
1.
6. The preparation method according to any one of claims 3 to 5, characterized in that: Step 3: The activation and reconstruction process of the nickel-iron-based square acid complex precursor is realized in an alkaline electrolyte by cyclic voltammetry.
7. The preparation method according to claim 6, characterized in that: The alkaline electrolyte is 1 mol / L potassium hydroxide; the activation voltage range is 1 to 1.45 V vs. RHE, and the activation is performed for 10 to 50 cycles.
8. The preparation method according to any one of claims 3 to 7, characterized in that: The method also includes vacuum drying the nickel-iron-based double metal hydroxide derived from the square acid complex.
9. The preparation method according to claim 8, characterized in that: The drying temperature is 60-120° C. and the drying time is 12-15 hours.
10. An electrode comprising a water electrolysis oxygen evolution catalyst, wherein the water electrolysis oxygen evolution catalyst is a nickel-iron-based double metal hydroxide derived from the square acid complex according to claim 1 or 2.
Citation Information
Patent Citations
Preparation method of metal-containing three-dimensional graphitized carbon material and application of metal-containing three-dimensional graphitized carbon material in nitrate electrocatalytic reduction synthesis of ammonia
CN115058725A
CuCo2O4 / CoCu-MOF self-supporting flexible electrode and preparation method and application thereof
CN117434123A
Nickel-iron layered double hydroxide-loaded oxygen evolution electrode and preparation method thereof
CN117568847A
Preparation method of Ni-CoFe LDHs alkaline electrolysis water oxygen evolution catalyst
CN118186489A
Tow dolly assembly
KR1020250162992A